PELATIHAN STRATEGI BERHITUNG CEPAT DALAM MATEMATIKA - Matondang, Khoiruddin; Saragih, Risna Mira Bella; Rizqi, Nur Rahmi; Nisa, Rahmi Khoirun (Fakultas Keguruan dan Ilmu Pendidikan UNIVA Medan, 2024)
The ability to count quickly is an important basic skill in learning mathematics, especially for Vocational High School (SMK) students who are prepared for the world of work. However, many students still experience difficulties in solving math problems efficiently due to low quick counting skills, lack of implementation of innovative learning strategies, and low motivation to learn mathematics. This research aims to provide training on quick counting strategies to students of SMK Telkom 1 Medan to improve their competence in solving math problems quickly and accurately, as well as change their mindset towards mathematics. The research method used is training, which consists of several stages, namely problem identification, learning strategy design, training implementation, and evaluation of training results. The results of the study show that students show high enthusiasm in participating in this training. In addition, there is a significant change in the mindset of students, from initially considering mathematics as a difficult and boring subject to more fun and challenging. The evaluation of the training results also showed an improvement in students' quick counting skills, both in terms of speed and accuracy of problem solving. Thus, this quick counting strategy training has proven to be effective in improving students' mathematical competence, building their confidence, and having a positive impact on their readiness in the academic and work worlds. The success of this program can be a model for other schools in improving their quick numeracy skills and interest in learning mathematics among vocational school students.